PARENTING SEMINAR: UNDERSTANDING CHILDREN’S CHARACTER, POTENTIAL, AND LOVE RESERVES AS A PREVENTIVE MEASURE IN STRENGTHENING THE EMOTIONAL MENTALITY OF YOUNG CHILDREN - Sari Harahap, Angginun Juwita; Intan, Bella; Mustofa, Arya; Azhar, Agung; Khairunnisa, Rizky; Irman, Adi; Fajrin, Nurul; Ripki, Yuda; Nadwah, Izaazun; Ramadhandi, Simbar; Primarni, Amie; Maharani, Anissa (Jurnal Pengabdian West Science, 2025)
This article is motivated by the increasing complexity of child-rearing challenges in the modern era, when parents often find it difficult to understand their children’s unique characteristics. The purpose of this paper is to analyze the effectiveness of parenting seminars with three main focuses: recognizing temperament, identifying potential through multiple intelligences, and fulfilling the need for affection with the concept of “affection battery.” The method used is a literature review with a descriptive qualitative approach through the study of developmental psychology and parenting theories. The results of the analysis show that understanding children’s temperaments helps parents apply appropriate parenting patterns, thereby reducing conflict and negative labeling. The perspective of multiple intelligences broadens parents’ view that their children’s potential goes beyond academic aspects. Meanwhile, meeting the need for affection through the "Language of Love" builds secure attachment and emotional health. It is concluded that parenting seminars that integrate these three aspects are effective preventive interventions and should be disseminated to increase collective awareness of the importance of parenting based on understanding the individual child.